TEACHING GREEN ENGINEERING PRINCIPLES AND APPLICATION THROUGH ACTIVE LEARNING - Tony Hadibarata (Sanata Dharma University Yogyakarta, 2019)
Active learning refers any approach to instruction in which all students are required to involve in the learning process. The purpose of the manuscript is to evaluate the application of active learning in teaching Green Engineering Principles and Applications as a compulsory course in environmental engineering department curriculum, Curtin University Malaysia. Green engineering can be defined as an approach of the design, process, product and commercialization that follow environmentally conscious attitude, principles and values combined with multi-disciplinary engineering science that to minimize pollutant and promote local and global sustainability. Green engineering encompasses the conceptualization and implementation of reducing environmental impacts, maximize energy efficiency and develop the greener processes and product that bring environmental and economic benefit. A simple approach that combining the classical lecture-presentation and active engagement of the students with the course materials through case studies, problem solving and discussion has been developed. In conclusion, introducing the active learning to the students on solving any problems improve the students’ ability in achieving the course outcome and thus the programme outcome of the Department of Environmental Engineering, Curtin University Malaysia.